2017
DOI: 10.4238/gmr16019327
|View full text |Cite
|
Sign up to set email alerts
|

MiR-214 regulates oral cancer KB cell apoptosis through targeting RASSF5

Abstract: ABSTRACT. Ras association domain family member 5 (RASSF5), a member of the Ras association domain family, induces cell apoptosis by phosphorylating FOXO3a, which triggers target gene BIM (proapoptotic factor) activation. MiR-214 is overexpressed in oral cancer tissue, indicating its possible involvement in oral cancer pathogenesis. Bioinformatics analysis has revealed a complimentary sequence between miR-214 and the 3'-UTR of RASSF5 mRNA. However, whether miR-124 regulates RASSF5 in oral cancer remains poorly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Moreover, it is of particular interest that the second relevant prognostic mature miRNA in our study, miR‐214‐3p, derives from the stem loop sequence of mir‐214 that clusters with mir‐199a‐2 of the same chromosome locus 1q24.3. Similar to miR‐199a‐3p, miR‐214‐3p acts, depending on the cancer types, oncogenic in osteosarcoma and oral cancer but tumor suppressive in breast, cervical, esophageal, and bladder cancers . Based on our previous expression study , Wang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is of particular interest that the second relevant prognostic mature miRNA in our study, miR‐214‐3p, derives from the stem loop sequence of mir‐214 that clusters with mir‐199a‐2 of the same chromosome locus 1q24.3. Similar to miR‐199a‐3p, miR‐214‐3p acts, depending on the cancer types, oncogenic in osteosarcoma and oral cancer but tumor suppressive in breast, cervical, esophageal, and bladder cancers . Based on our previous expression study , Wang et al.…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, miRs can promote the degradation of target gene mRNA at the posttranscriptional level; on the other hand, they can inhibit gene translation and eventually lead to the silencing of the target gene (3,7). According to the different targeting effects, miRs can act as oncogenes or tumor suppressor genes in the progression of a number of malignant tumors (8). miRs have their own specific expression profiles in different tissues and are abnormally expressed in different tumors, resulting in their gradual application as prognostic indicators of cancer (9).…”
Section: Introductionmentioning
confidence: 99%
“…Cellular Physiology and Biochemistry and pancreatic cancer and its down-regulation resulted in the inhibition of cell apoptosis [27,28]. However, recent report suggested that miR-214 was down-regulated in cervical tumor tissues and cancer cells, and up-regulation of miR-214 leaded to the inhibition of cell growth, migration and invasion of cervical cancer cells and prompted the sensitivity to cisplatin [29,30].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…Furthermore, this study discovered that miR-214 overexpression suppressed the proliferation of CRC cells. Numerous studies have provided the evidence that miR-214 could changed biological functions of different cancer cells by its targets such as fibroblast growth factor receptor 1 (FGFR1), forkhead box M1 (FOXM1), Ras association domain family member 5 (RASSF5), Plexin-B1, phosphatase and tensin homolog (PTEN), and Ring finger and WD domain 2 (RFWD2) [27][28][29][30][31][32][33][34][35]. TFAM is a molecule which is essential for mtDNA replication and transcription, as well as mtDNA maintenance [36,37].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%